Graphic Requirements for Multiple Attractive Cycles in Boolean Dynamical Systems - Dong, Jian-Lang (Journal of Informatics and Mathematical Sciences, 2011)
E. Remy, P. Ruet and D. Thieffry have proved a Boolean version of Thomas' conjecture: if a map $F$ from $\{0,1\}^{n}$ to itself has several fixed points, then there exists a positive circuit in the corresponding interaction graph. In this paper, we prove that the presence of a positive circuit in a local interaction graph is also a necessary condition for the presence of several attractive cycles in the Boolean synchronous dynamics.